Application of an assisted discovery learning Model e-lkpd to improve geography learning outcomes class x at sman 2 sungai rumbai dharmasraya regency - Efrianti, Delli Hardianti; Anwar, Syafri (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
ABSTRACT This research aims to, 1) determine students' learning activities in geography learning by applying the discovery learning model assisted by E-LKPD class E-LKPD class X at SMAN 2 Sungai Rumbai. The research carried out is classroom action research (Class-room Action Research). This classroom action research (PTK) was carried out in the even semester of the 2022/2023 academic year. The research was carried out in three cycles. The subjects in this research were class X science students with a total of 14 students. Data collection techniques use observation, learning motivation observation sheets, tests, and documentation. Data were analyzed using percentages and data reduction. The research results show that, 1) students' learning activities by implementing the Discovery Learning model assisted by E-LKPD in each cycle have succeeded in increasing. This can be seen from the increase in the grades of class X Science students at SMAN 2 Sungai Rumbai from cycle to cycle. In cycle I the level of student activity was in the sufficient category, then in cycle II it was in the good category, and increased in cycle III, namely in the very good category, 2) learning by applying the discovery learning model assisted by E-LKPD can improve Learning outcomes of class In cycle I, there were 6 students who completed it or 43%, then it increased in cycle II to 9 people or 64%, and 12 people or 86% reached the completion criteria set in cycle III. This means that there is an increase in each cycle of student learning outcomes in Geography learning by implementing the Discovery Learning learning model assisted by E-LKPD. Keywords: discovery learning, E-LKPD, learning outcomes, geography